Detection of Mycobacterium tuberculosis in smear negative sputum by PCR (Bangladesh Journal of Medical Microbiology, 2012)
Pulmonary tuberculosis is a major health problem in Bangladesh that is responsible for about 7% of total death in a year. This study was conducted to isolate and identify Mycobacterium tuberculosis from sputum and to evaluate the efficacy of PCR as a modern diagnostic tool, for diagnosis of pulmonary tuberculosis, especially in the smear negative cases. One hundred and fifty suspected pulmonary TB patients (male/ female: 97/53) were included in this study. Single morning sputum was collected from each patient and diagnostic potential of PCR was compared with staining and culture. Twenty five (16.7%) sputum were positive by ZN stained smear. Among 125 smear negative samples, 13 (10.4%) yielded growth in culture in LJ media and 21 (16.8%) samples were positive by PCR. The sensitivity and specificity of PCR in smear negative cases was 100% and 92.9% respectively. Mean detection time in PCR was 24 hours. PCR detected M. tuberculosis in 21 smear negative and 9 culture negative samples. For diagnosis of tuberculosis in smear negative cases, PCR directly from sputum was a very sensitive and accurate method. In conclusion, PCR may be done, especially in clinically suspected pulmonary tuberculosis patients who remain negative by conventional methods.DOI: http://dx.doi.org/10.3329/bjmm.v6i2.19368 Bangladesh J Med Microbiol 2012; 06(02): 2-6